For a Safer City. A Friendlier City. And a More Beautiful City. - Busi, Roberto (TeMA - Journal of Land Use, Mobility and Environment, 2010)
The issue of the safety of mobility in the urban environment has been emerging as a primary social topic for some time now due to the number of casualties and, more generally, due to the impact on living conditions in the city.If correctly formulated, in fact, this subject has implications primarily and fundamentally with regard to the quality of urban life, as the citizen, and the vulnerable road user in particular, is severely restricted in their use of urban public paces. Consequently, an increasingly greater focus is being placed on acquiring methods, techniques and strategies for addressing the issue of planning, constructing and managing roads, squares and urban green spaces (and above all, applying the logic of reclaiming the historic and consolidated city) in order that the city can be used to its full potential by the citizen. The subject itself therefore presents an opportunity to re-establish urban planning regulations (and, more generally, city regulations) in accordance with the renewed interest in public spaces.The article discusses this matter and includes supporting elements and examples, also referring to the implications on the urban landscape.